Complete chloroplast sequence of common groundsel (Senecio vulgaris Subsp. vulgaris) - Kim, Jin-Won (Mitochondrial DNA B Resour, 2019)
Senecio vulgaris is an exotic annual winter weed that is problematic in garlic and onion fields in Republic of Korea. The chloroplast DNA was 150,765 bp with 82,907 bp of large single-copy region, 18,214 bp of small single-copy region, and 24,822 bp of a pair of inverted repeats. A total of 104 genes were annotated including 80 protein-coding genes, 20 tRNA genes, and 4 rRNA genes. Twelve genes (ClpP, ndhB, ycf3, rpl2, rps12, trnA, trnI, trnR, trnG, trnL, and trnV) were multiple-copy genes. Senecio vulgaris was closely related to Jacobaea vulgaris in same subfamily resulting from phylogenetic analysis.